The El - Van Alst, Theodore C., 1965- (Vintage Books, a division of Penguin Random House LLC, 2025)
"An ordinary day in August 1979 dawns hot and humid in Chicago. Teenager Teddy is living with his dad after being kicked out of his mom's house due to his gang activity. But Teddy has thrived in the Simon City Royals, and today, he'll be helping to lead a posse of the group's younger members south across the city to Roosevelt High School to attend a gathering of gangs forming "the Nation"--a bold new attempt at joining forces across racial lines. This holds particular importance for Teddy, as his branch's only Indigenous member. But when the meeting breaks up in gunshots and police sirens, Teddy must guide the Royals back across hostile territory, along secret routes and back alleys, and stop by stop on the thundering tracks of the El. In the face of violence from rival gangs and a secret Judas in the Royals' ranks, Teddy is armed only with a potent combination of book smarts and street smarts, and by the guiding spirit of Coyote, who has granted him the power to glimpse a future only he may survive to see. Immersed in the sights, sounds, and smells of the author's beloved city, The El will transport you to that singular sun- and blood-soaked day in Chicago. It is a love letter to another time, to a city, and to a group of friends trying to find their place and make their way in a world that doesn't want them."--Page 4 of cover.